Larry Saves the Canadian Healthcare System: Research-based musical satire goes digital - Kreindler, Sara (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
Larry Saves the Canadian Healthcare System is a research-based satirical musical tackling fundamental health policy issues. This companion text describes Larry’s content, style, and educational intent. It also tells the story of the piece’s development, including its pivot to video due to the COVID-19 pandemic and its evolution following initial audience reception.